2012
DOI: 10.1587/elex.9.1473
|View full text |Cite
|
Sign up to set email alerts
|

Phase noise analysis of an optical frequency comb using single side-band suppressed carrier modulation in an amplified optical fiber loop

Abstract: Coherent optical two-tone generation using an optical frequency comb generator based on an amplified optical fiber loop is successfully demonstrated. The observed phase noises in the 100-GHz band are less than −80 dBc/Hz at 1 MHz. This method is suitable for high-speed radio communication based on advanced modulation techniques. Keywords: radio over fiber, optical frequency comb, phase noise Classification: Fiber optics, Microwave photonics, Optical interconnection, Photonic signal processing, Photonic integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…OSN R e f f (dB) ≈ 10log(10 ) ) (24) In addition to the effect of seed laser linewidth [183] on the quality of OFC, phase noise characteristics of the comb lines and their relationship with frequency spacing [184] have also been studied. Yu et al demonstrated a 90 line OFC, having 4.26 dB amplitude variation, by optimizing the length and gain of the loop using additional variable optical attenuator (VOA) and delay lines [185].…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…OSN R e f f (dB) ≈ 10log(10 ) ) (24) In addition to the effect of seed laser linewidth [183] on the quality of OFC, phase noise characteristics of the comb lines and their relationship with frequency spacing [184] have also been studied. Yu et al demonstrated a 90 line OFC, having 4.26 dB amplitude variation, by optimizing the length and gain of the loop using additional variable optical attenuator (VOA) and delay lines [185].…”
Section: )mentioning
confidence: 99%
“…Sum Frequency Generation (SFG): SFG effect combines two photons at λ P and λ S to generate a third photon at λ SFG , where : [192], [195] 4 Comb enabled Terabit transmission [72], [181], [195], [196] 5 RFS Comb Stability and quality [178], [183], [191] 6 Crosstalk [179], [182] 7 Flatness [180], [183], [194] 8 Phase noise [184] 9 TNR and lines [185], [186], [187], [188], [190], [189] 10 Multi-frequency shifting [186], [187] 11 Dual loops [188], [193], [194] 12 complexity and cost [193], [194] 13 Noise Suppression [189], [190] From energy conservation perspective, one photon at frequency f P and one photon at frequency f S are annihilated by two photon absorption and the atom jumps to higher (virtual) energy level. Subsequently, a photon at f SFG = f P + f S is generated and the atom drops back to original state [199].…”
Section: B Combs Based On Nonlinearities In Periodically Poled Lithimentioning
confidence: 99%
“…In this paper, for a proof-of-concept demonstration, we demonstrate a recirculating frequency shifter in an amplified optical fiber loop for OFC signal generation (Fig. 3) [31], [32]. An optical frequency shifter, which is based on an optical single-sideband (SSB) suppressed-carrier (SSB-SC) modulator connected to a local oscillator (LO), changes an optical frequency of the input optical signal with the frequency of the LO signal [33].…”
Section: Configuration Of An Optical Subharmonic Mixermentioning
confidence: 99%
“…NE of the most useful attributes of microwave photonics technology is the availability of high bandwidth photodetection, which consequently enables the generation of microwave, mm-wave and THz signals through a variety of topologies and devices [1] [2]. This ranges from the use of discrete devices as in mode-locked lasers [3], gain-switched lasers [4], external modulation [5] [6], and nonlinear optics [7] to generate optical combs, through to more complex topologies such as optoelectronic oscillators (OEOs) [8] and recirculating optical loops [9]. In all cases the motivation is the feasibility of producing a signal directly in the optical domain, allowing it to be distributed and processed photonically.…”
Section: Introductionmentioning
confidence: 99%